2021
DOI: 10.36660/abc.20200546
|View full text |Cite
|
Sign up to set email alerts
|

Retenção das Habilidades de Ressuscitação Cardiopulmonar nos Estudantes de Medicina

Abstract: Fundamento: A redução da mortalidade e das sequelas de uma vítima de parada cardíaca depende de um atendimento eficaz, rápido e iniciado o mais precocemente possível. O suporte básico de vida (SBV) compreende uma série de etapas que podem ser iniciadas fora do ambiente hospitalar, e ensinadas para qualquer pessoa em cursos específicos. Porém, é importante que o socorrista retenha o conhecimento e as habilidades, pois nunca se sabe quando será necessário realizar uma ressuscitação cardiopulmonar (RCP). Entretan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These initial steps in CPR are often di cult and stressful, particularly for inexperienced rst responders and medical personnel. Furthermore, previous studies have shown that resuscitation skills deteriorate in most medical personnel (e.g., medical and nursing students) over time [13,14], being most evident after 6 months following training completion [13]. Other personal characteristics (e.g., leadership ability, personality, and sex) also have a large impact on CPR algorithm adherence and team dynamics [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…These initial steps in CPR are often di cult and stressful, particularly for inexperienced rst responders and medical personnel. Furthermore, previous studies have shown that resuscitation skills deteriorate in most medical personnel (e.g., medical and nursing students) over time [13,14], being most evident after 6 months following training completion [13]. Other personal characteristics (e.g., leadership ability, personality, and sex) also have a large impact on CPR algorithm adherence and team dynamics [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The disappointing results regarding resuscitation skills reported by many studies are probably linked to skill and information retention. Indeed, it has been shown that BLS-AED skills and knowledge decrease significantly within months after the last training session [ 23 , 24 ]. The same issue affects advanced life support skills among anesthetists [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to CPR, 66.7% of the students consider themselves capable of performing it. In a study on the retention of CPR skills with medical students 17 , where the skills were checked after a course and six months after it, retention showed a reduced value at the second moment. Considering a time interval of approximately one year between having learned the skills in the first semester curricular class and participating in this study, the number of students who feel capable is also small.…”
Section: Discussionmentioning
confidence: 99%